О направлениях исследований развития импортозамещающей техники для лесосечных работ - Skrypnik V. I., Kuznetsov A. V., Vasilyev A. S. (Scientific studies: from theory to practice, 2016)
shows that important areas of technology research for logging activities are the rationale for the effective parameters and modes of operation, ensuring the rational development of cutting areas, the creation of new competitive technology facilities.
Keywords: исследования; машины; лесосечные работы; research; machine; logging work